Impact of macro-socioeconomic determinants on sustainable perinatal health care in Portugal: a qualitative study on the opinion of healthcare professionals and experts - Julia Nadine Doetsch; Sandra C. S. Marques; Thomas Krafft; Henrique Barros (BMC, 2021)
Abstract Background The WHO identified the importance of macro-socioeconomic determinants and political context as interlinked key factors affecting healthcare quality and health equity. As a response to the recent economic and financial crisis, Portugal approved in 2011 the Economic Adjustment Programme (EAP) to obtain financial assistance from the Troika in order to reduce public debt. This study aims to analyse the impact of the economic crisis and the EAP on perinatal healthcare quality for very preterm (VPT) and/or very low birth weight (VLBW) infants, as perceived by healthcare professionals and experts, within the health administrative regions of the two major metropolitan areas in Portugal. Methods A qualitative approach was applied to receive an in-depth understanding and accomplish perspective variability. A purposive sampling technique was used. Semi-structured interviews were conducted with twenty-one healthcare professionals and experts between October 2018-July 2019. Inductive thematic analysis was performed which encompassed a five-step categorization procedure. Data analysis was undertaken by utilizing Nvivo2011 software. Evolved themes were then associated with WHO's Quality Standards on Maternal and New-born Care. A framework on the impact of macro-socioeconomic determinants on perinatal health care quality was developed. Results Although participants did not perceive the quality of perinatal care had deteriorated, the analysis of their accounts on work experience revealed that it was indeed adversely modified in all WHO Quality Standards. Health care provision was perceived as detrimental in five main areas: 1) Availability of human resources; 2) Functional referral systems; 3) Competent and motivated human resources; 4) Emotional support; and 5) Essential physical resources available. Policy reforms by the EAP resulted in reduced timeliness of care, increased waiting times, cuts in sequence and duration of consultations, and deficiencies in follow-up care for VPT/VLBW infants and their mothers. The EAP directly influenced working environment of healthcare professionals by causing stress, burnout, work absence, and brain drain. Conclusion An interrelation between macro-socioeconomic determinants and perinatal health care quality was disclosed. The economic crisis and EAP have adversely modified equitable perinatal health care quality for VPT/VLBW infants and their mothers. Our findings underlined the negative impact of austerity policies on vulnerable populations.